Answer:
Ellie needs 1.2 or 1 1/5 cups of flour (as 2/10 simplifies to 1/5).
Please mark me brainliest if this helped!
to get the equation of any straight line all we need is two points, well, let's just grab them from the table.
hmmm let's use (-49 , -39) and hmmm say (67 , 77)
![(\stackrel{x_1}{-49}~,~\stackrel{y_1}{-39})\qquad (\stackrel{x_2}{67}~,~\stackrel{y_2}{77}) \\\\\\ \stackrel{slope}{m}\implies \cfrac{\stackrel{rise} {\stackrel{y_2}{77}-\stackrel{y1}{(-39)}}}{\underset{run} {\underset{x_2}{67}-\underset{x_1}{(-49)}}}\implies \cfrac{77+39}{67+49}\implies \cfrac{116}{116}\implies 1](https://tex.z-dn.net/?f=%28%5Cstackrel%7Bx_1%7D%7B-49%7D~%2C~%5Cstackrel%7By_1%7D%7B-39%7D%29%5Cqquad%20%28%5Cstackrel%7Bx_2%7D%7B67%7D~%2C~%5Cstackrel%7By_2%7D%7B77%7D%29%20%5C%5C%5C%5C%5C%5C%20%5Cstackrel%7Bslope%7D%7Bm%7D%5Cimplies%20%5Ccfrac%7B%5Cstackrel%7Brise%7D%20%7B%5Cstackrel%7By_2%7D%7B77%7D-%5Cstackrel%7By1%7D%7B%28-39%29%7D%7D%7D%7B%5Cunderset%7Brun%7D%20%7B%5Cunderset%7Bx_2%7D%7B67%7D-%5Cunderset%7Bx_1%7D%7B%28-49%29%7D%7D%7D%5Cimplies%20%5Ccfrac%7B77%2B39%7D%7B67%2B49%7D%5Cimplies%20%5Ccfrac%7B116%7D%7B116%7D%5Cimplies%201)
![\begin{array}{|c|ll} \cline{1-1} \textit{point-slope form}\\ \cline{1-1} \\ y-y_1=m(x-x_1) \\\\ \cline{1-1} \end{array}\implies y-\stackrel{y_1}{(-39)}=\stackrel{m}{1}(x-\stackrel{x_1}{(-49)}) \\\\\\ y+39=1(x+49)\implies y+39=x+49\implies y=x+10](https://tex.z-dn.net/?f=%5Cbegin%7Barray%7D%7B%7Cc%7Cll%7D%20%5Ccline%7B1-1%7D%20%5Ctextit%7Bpoint-slope%20form%7D%5C%5C%20%5Ccline%7B1-1%7D%20%5C%5C%20y-y_1%3Dm%28x-x_1%29%20%5C%5C%5C%5C%20%5Ccline%7B1-1%7D%20%5Cend%7Barray%7D%5Cimplies%20y-%5Cstackrel%7By_1%7D%7B%28-39%29%7D%3D%5Cstackrel%7Bm%7D%7B1%7D%28x-%5Cstackrel%7Bx_1%7D%7B%28-49%29%7D%29%20%5C%5C%5C%5C%5C%5C%20y%2B39%3D1%28x%2B49%29%5Cimplies%20y%2B39%3Dx%2B49%5Cimplies%20y%3Dx%2B10)
Answer:
6
Step-by-step explanation:
add 11 to both sides, that cancels out so then your left with 7x=42, divide by 7 on both sides then you should get x=6
Answer:
-3
Step-by-step explanation:
Because f(x) = y so when y=3 what is input value (x)
When y is 3 x is -3